Cobaltite-rich mineralization in the iron skarn deposit of Traversella (Western Alps, Italy). (February 2014) - Nimis, P.; Dalla Costa, L.; Guastoni, A.
Abstract: Cobaltite-rich mineralization from the iron skarns of the Traversella magnetite mine (Western Alps, Italy) was studied by reflected-light microscopy, scanning electron microscopy and electron microprobe analysis. Cobaltite is found in carbonate-chlorite-rich rocks at the margins of the main magnetite masses, where it forms disseminations and metasomatic veinlets that postdate the formation of magnetite. The paragenesis includes cobaltite (± arsenopyrite), bismuthinite, pyrrhotite and/or pyrite, chalcopyrite, carbonates, talc, chlorite and native gold, and is indicative of a low-sulfidation environment. The sulfarsenides show oscillatory and sector zoning, which indicates disequilibrium during crystal growth. Compositional variations are mainly due to variations in the Co/Fe ratio of arsenopyrite and in either the Co/Fe or the Ni/(Fe + Co) ratios of the coexisting cobaltite. The Ni contents are low to very low in the cobaltites (<2.4 wt.%) and very low in the arsenopyrites (<0.16 wt.%). The As/S molar ratios in the cobaltites are highly variable (0.59−1.00) and show a broad negative correlation with the Fe contents. The formation of cobaltite is related to circulation of relatively low-temperature (<∼300°C), (Co, As, Bi)-rich fluids during the retrograde sulfidation stage which followed the formation of magnetite. The apparent restriction of cobaltite (+ bismuthinite ± arsenopyrite) to the margins of the main magnetite columns may reflect the establishment of thermochemical gradients around the main direction of infiltration of the retrograde metasomatic fluids.